Hubungan Antara Persepsi Terhadap Program CSR (Corporate Social Responsibility) dengan SWB (Subjective Well Being) pada Komunitas X di Yogyakarta - Antoni Firdaus; Muslimah Zahro Romas; Dewi Handayani Harahap (LPPM Universitas Proklamasi 45, 2021)
Subjective Well Being (SWB) is a subjective assessment of one's life experience, which consists of a cognitive evaluation of satisfaction with life, happiness, peace, fulfillment of needs and affective assessment of positive and negative emotions. Corporate Social Responsibility (CSR) is a series of activities arranged and planned in the form of social responsibility from an organization or company as a form of contribution and directed to (internal) and external (external) to the company. Aims: This study aims to determine the relationship between the perceptions of the Corporate Social Responsibility (CSR) program with Subjective Well Being (SWB) in the community in the X Village of Yogyakarta. Method of this study is to use quantitative method. The subjects in this study were the communities around companies affected by CSR programs. Sampling is done by using conventional sampling (convenience sampling). The validity used is construct validity with the calculation of Product Moment Correlation developed by Karl Pearson with the help of SPSS. The results of this study are that there is a positive relationship between corporate social responsibility and Subjective Well Being can be accepted. This is indicated by the value of rxy 0.570 with a significance level obtained p = 0,000 <001.The existence of a very significant positive relationship between Corporate social responsibility and Subjective Well Being can be accepted. This means that the higher the value of the corporate social responsibility program, the higher the Subjective Well Being. Conversely the lower the value of the corporate social responsibility program, the lower the Subjective Well Being.